Viscoelastic and Thermal Characterization of a Composite Material Based on Unsaturated Polyester Resin Reinforced with Perlite - Dehas Ouided; Biskri Yasmina; Benzerara Mohammed; Babouri Laidi; Cherifi Acheref (Selected Scientific Papers: Journal of Civil Engineering)
In this work, it was proposed to replace the conventional reinforcement of the unsaturated polyester resin by a mineral, from a siliceous volcanic rock of volcanic nature, perlite. UPR/perlite composites with different proportions of phase components (from 1% to 5% of powder mass part). We used unsaturated polyester resin (UPR) as well as the hardener cobalt octoate and treated and untreated perlite of different dimensions (greater than 60µm, and less than 60µm). The composites were prepared by the contact molding process. The composite plates are hardened for 24 hours at room temperature then placed in an oven for 15 hours at 50°C to undergo post-curing. The composites obtained were subjected to different characterization techniques, namely rheological tests (dynamic mechanical analysis (DMA)), thermal tests (differential calorimetric analysis (DSC)) and Thermogravimetric analysis (ATG) and structural characterization by Fourier transform infrared (FTIR). The DMA measurements showed that the UPR/perlite composites with untreated filler presented conservation modules higher than that of the resin without perlite for the rates of 3% and 4%, while for the composites with treated filler, that at 3% of perlite shown the highest modulus along the glassy zone. Also, the glass transition temperature of the UPR resin was not affected by the addition of perlite. The decrease in intensity at mid-height of the tan δ peaks allowed deducing the existence of a fairly strong UPR/perlite interface. DSC thermograms showed that the exothermic peak is shifted to higher temperatures, due to a delay in the curing reaction caused by the presence of the perlite particles. This study concluded that the perlite enhances the properties of composites.